2013
DOI: 10.1002/14651858.cd008391.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation for executive dysfunction in adults with stroke or other adult non-progressive acquired brain damage

Abstract: Background Executive functions are the controlling mechanisms of the brain and include the processes of planning, initiation, organisation, inhibition, problem solving, self monitoring and error correction. They are essential for goal-oriented behaviour and responding to new and novel situations. A high number of people with acquired brain injury, including around 75% of stroke survivors, will experience executive dysfunction. Executive dysfunction reduces capacity to regain independence in activities of daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 52 publications
2
143
0
1
Order By: Relevance
“…• That a direct comparison of memory training in virtual environments versus nonvirtual environments is still lacking and no recommendation can be made as to the specificity of the technique An updated review of the literature (2003-2008) 418 concluded that (1) for individuals with mild memory impairments, memory strategy training, including the use of internalized strategies (eg, visual imagery) and external memory compensations (eg, notebooks), is recommended as a practice standard; (2) for individuals with severe memory deficits, the use of external compensations, including assistive technology, with direct application to functional activities is recommended as a practice guideline; and (3) for individuals with severe memory impairments, errorless learning techniques may be effective for learning specific skills or knowledge, although with limited transfer to novel tasks or reduction in overall functional memory problems However, a recent Cochrane meta-analysis 425 with 13 cognitive rehabilitation RCTs reported no benefit to executive functioning after stroke, whereas other systematic reviews using a broader range of evidence have suggested some limited evidence. 426,427 Current studies are small and have highly varied content, making comparisons difficult.…”
Section: Nondrug Therapies For Cognitive Impairment Including Memorymentioning
confidence: 99%
“…• That a direct comparison of memory training in virtual environments versus nonvirtual environments is still lacking and no recommendation can be made as to the specificity of the technique An updated review of the literature (2003-2008) 418 concluded that (1) for individuals with mild memory impairments, memory strategy training, including the use of internalized strategies (eg, visual imagery) and external memory compensations (eg, notebooks), is recommended as a practice standard; (2) for individuals with severe memory deficits, the use of external compensations, including assistive technology, with direct application to functional activities is recommended as a practice guideline; and (3) for individuals with severe memory impairments, errorless learning techniques may be effective for learning specific skills or knowledge, although with limited transfer to novel tasks or reduction in overall functional memory problems However, a recent Cochrane meta-analysis 425 with 13 cognitive rehabilitation RCTs reported no benefit to executive functioning after stroke, whereas other systematic reviews using a broader range of evidence have suggested some limited evidence. 426,427 Current studies are small and have highly varied content, making comparisons difficult.…”
Section: Nondrug Therapies For Cognitive Impairment Including Memorymentioning
confidence: 99%
“…However, the requirement that a patient must be able to produce brain responses as prescribed by study instructions to demonstrate that he/she is aware is likely too stringent for many patients who are aware but, due to the effects of brain injury, fail to comply with structured instructions (35,46,47). Up to 43% of patients, who on the basis of routine bedside assessment are declared to be in a vegetative state (34), show inconsistent but reproducible behavioral signs of awareness to more careful/intensive bedside assessments (48) and are reclassified as being in a minimally conscious state (35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that patients benefit from recommendations of physical exercise. 39 They may also benefit from cognitive rehabilitation training 40 and pharmacological therapy with acetylcholinesterase inhibitors. 41 …”
Section: Strokementioning
confidence: 99%